Aminoquinoline-assisted vinylic C–H arylation of unsubstituted acrylamide for the selective synthesis of Z olefins. Issue 12 (2nd March 2016) - Cheng, Xiuzhi; Chen, Zhen; Gao, Yadong; Xue, Fengtian; Jiang, Chao
Abstract : A method for Pd-catalyzed, aminoquinoline-directed arylation of vinylic C–H bonds with aryl iodides has been developed. This reaction represents a rare example of Pd-catalyzed vinylic C–H functionalization of unsubstituted acrylamide, allowing for preparation of Z -olefins. Abstract : A method for Pd-catalyzed, aminoquinoline-directed arylation of vinylic C–H bonds with aryl iodides has been developed. This reaction represents a rare example of Pd-catalyzed vinylic C–H functionalization of unsubstituted acrylamide, allowing for the highly regio- and stereoselective preparation of Z -olefins. High tolerance to functional groups is observed with good yields and excellent selectivity. It offers a complementary synthetic method to traditional pathways for Z -olefins.